Pengaruh Model Pembelajaran Problem Solving dengan Puzzle terhadap Kemampuan Kognitif Anak Usia 5-6 tahun - Azizah, Nanda Nila robmatul; haroh, Muto (Al Athfal : Jurnal Kajian Perkembangan Anak dan Manajemen Pendidikan Usia Dini, 2023)
Research conducted on students at TK PERTIWI 01 GENENGMULYO was motivated by low cognitive abilities in learning Problem Solving. This is because teachers at PERTIWI 01 GENENGMULYO Kindergarten still use worksheets in PUZZLE learning such as maze and complete pictures that are lacking so that some children do not understand how to solve real problems. In addition, learning is still monotonous and causes a lack of interest in children. This study uses a quantitative research approach. The subjects in this study were TK B students at TK PERTIWI 01 GENENGMULYO with a total of 30 subjects. The data collection technique used was by giving questionnaires to teachers from Kindergarten B. And the data analysis technique used was descriptive statistical analysis, Pearson Correlation, and Regression. The correlation coefficient value is 0.31 which means it has a moderate relationship, and the R2 value is 72.27 or 72% of the contribution of the variable x to Y. The calculated t value is 0.17 while the t table value is 1.699. This means that there is a significant influence between puzzle games on children's problem solving learning.